Intermediate Treatment Facility as a Waste Management System in DKI Jakarta: An Overview - Angelia, Lisa; Firmansyah, Amrie; Meidian, Perdana Riffi; Chaniago, Putri Rieza; Suhendra, Maman (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
The limited capacity of the Bantargebang landfill as the final waste disposal site and the ever-growing amount of waste produced by Jakartans urges the development of more eco-friendly waste management facilities. Using the scoping review method, this study aims to review the feasibility of ITF development in DKI Jakarta based on identifiable impacts, social costs and benefits analysis, hindrances faced in ITF development planning, and reviewing alternative financing that can be used in constructing ITF. The results of this study show that aside from its capacity to process waste more efficiently and potentially produce electricity, ITF construction may have several negative impacts on the surrounding environment. Based on an analysis of social costs and benefits, the development of ITF is feasible. However, some obstacles are present in planning the development of ITF, such as that it requires a strong investment commitment in terms of financing development and project operations, both from the DKI Jakarta Provincial Government, DPRD, and the private sector. Two possible financing schemes to consider are the local government budget and PPP.